2019
DOI: 10.1016/s2352-4642(19)30246-9
|View full text |Cite
|
Sign up to set email alerts
|

Underdetection of laboratory-confirmed influenza-associated hospital admissions among infants: a multicentre, prospective study

Abstract: Background-Since influenza often presents non-specifically in infancy, we aimed to assess the extent to which existing respiratory surveillance platforms might underestimate the frequency of severe influenza disease among infants.Methods-The Influenza and Respiratory Syncytial Virus in Infants (IRIS) study was a prospective observational study done at four hospitals in Albania, Jordan, Nicaragua, and the Philippines. We included acutely ill infants aged younger than 1 year admitted to hospital within 10 days o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…In the latter study, seroconversion was more frequently observed in hospitalized patients, consistent with data from human challenge and COVID-19 studies [102] that suggest that severity of infection may correlate with the induction of antibody responses [95]. A recent multicenter study on the burden of respiratory infections in infants showed that 23% of influenza-positive infants did not seroconvert to the tested strains by HAI or microneutralization assays [103]. Overall, the correlation between the initial infection dose, disease severity, and antibody development is a challenge to address in any naturally-acquired infection studies due to difficulties in determining the time of infection.…”
Section: Antibody Non-responsiveness After Infectionsupporting
confidence: 81%
“…In the latter study, seroconversion was more frequently observed in hospitalized patients, consistent with data from human challenge and COVID-19 studies [102] that suggest that severity of infection may correlate with the induction of antibody responses [95]. A recent multicenter study on the burden of respiratory infections in infants showed that 23% of influenza-positive infants did not seroconvert to the tested strains by HAI or microneutralization assays [103]. Overall, the correlation between the initial infection dose, disease severity, and antibody development is a challenge to address in any naturally-acquired infection studies due to difficulties in determining the time of infection.…”
Section: Antibody Non-responsiveness After Infectionsupporting
confidence: 81%
“…In this study based on GBD 2019, we reported that the estimated incident cases of URIs reached more than 17 billion in 2019, accounting for about 43% cases of all the GBD diseases and injuries. As an important and common presentation for the reproduction and circulation of more than 200 known virus strains [ 23 , 24 ], the massive incidence of URIs may possess an unexpected threat to human health and should never be overlooked. The current pandemic of SARS-CoV-2, which presents mild URI syndromes in most of the patients, has led to severe diseases in some cases and caused more than three million deaths to date [25] .…”
Section: Discussionmentioning
confidence: 99%
“…Delayed presentation to healthcare facilities combined with a reliance on molecular testing can also lead to underestimations of burden. Indeed, a recent study that combined molecular and serological testing with wide testing criteria indicated that the burden of severe influenza in infants may be twice that of current global estimates (Thompson et al 2019). In addition, maternal influenza infection is associated with increased maternal morbidity and mortality, as well as increased occurrence of premature and small-for-gestational-age births.…”
mentioning
confidence: 99%